158k views
17 votes
Y=sqrt(x)(8x-5) find the derivative

Y=sqrt(x)(8x-5) find the derivative-example-1

1 Answer

0 votes

Answer:


\displaystyle y' = (24x - 5)/(2√(x))

General Formulas and Concepts:

Algebra I

  • Exponentials [Fractions] - Are radicals
  • Exponential Rule [Rewrite]:
    \displaystyle b^(-m) = (1)/(b^m)

Calculus

Derivatives

Derivative Notation

Derivative of a constant is 0

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Product Rule:
\displaystyle (d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Explanation:

Step 1: Define


\displaystyle y = √(x)(8x - 5)

Step 2: Differentiate


\displaystyle f(x) = √(x), \ g(x) = (8x - 5)

  1. Product Rule:
    \displaystyle y' = (d)/(dx)[√(x)] \cdot (8x - 5) + √(x) \cdot (d)/(dx)[(8x - 5)]
  2. Rewrite:
    \displaystyle y' = (d)/(dx)[x^{(1)/(2)}] \cdot (8x - 5) + √(x) \cdot (d)/(dx)[(8x - 5)]
  3. Basic Power Rule:
    \displaystyle y' = (1)/(2)x^{(1)/(2) - 1} \cdot (8x - 5) + √(x) \cdot 1 \cdot 8x^(1 - 1)
  4. Simplify:
    \displaystyle y' = (1)/(2)x^{-(1)/(2)} \cdot (8x - 5) + √(x) \cdot 1 \cdot 8x^(0)
  5. Rewrite:
    \displaystyle y' = \frac{1}{2x^{(1)/(2)}} \cdot (8x - 5) + √(x) \cdot 1 \cdot 8
  6. Multiply:
    \displaystyle y' = \frac{8x + 5}{2x^{(1)/(2)}} + 8√(x)
  7. Rewrite:
    \displaystyle y' = (8x + 5)/(2√(x)) + 8√(x)
  8. Add/Rewrite:
    \displaystyle y' = (24x - 5)/(2√(x))
User Vidhi Dave
by
5.0k points